Fluctuations of Oil Prices and Gross Domestic Product in Spain - Cantavella, Manuel (International Journal of Energy Economics and Policy, 2020)
The objective of this research is to analyze the asymmetric impact of crude oil prices on the real per capita gross domestic product (GDP) between 1945 and 2018 in Spain. The decomposition of oil prices into positive and negative partial sums in a nonlinear autoregressive distributed lag (NARDL) model allows examine the results derived from the fluctuations of oil prices in the international markets. The effects of those movements on per capita GDP are primarily long range, having the long-run oil price decreases a larger impact on the per capita GDP than the oil price increases. In spite of these asymmetric effects, the energy policy agenda should address some issues related to not only tax handling but to market competition and efficient wages mechanisms as well. Keywords: per capita GDP, asymmetric oil prices, NARDL, Spain JEL Classifications: C22, O40, Q41 DOI: https://doi.org/10.32479/ijeep.8806